Resposta funcional da joaninha cryptolaemus predando cochonilha branca em diferentes temperaturas e substratos vegetais - De Bortoli, Sergio Antonio [UNESP]; Gravena, Adriana Rossini [UNESP]; Vacari, Alessandra Marieli [UNESP]; De Laurentis, Valéria Lucas [UNESP]; De Bortoli, Caroline Placidi [UNESP] (My University, 2014)
This work was carried out to evaluate the functional response of Cryptolaemus montrouzieri Mulsant, 1850 (Coleoptera: Coccinellidae) fed with Planococcus citri Risso, 1813 (Hemiptera: Pseudococci-dae) reared on a pumpkin hybrid (Cucurbita maxima x Cucurbita moscata) (Cucurbitaceae), seedlings of Rang-pur lime (Citrus limonia) Rutaceae) and potato (Solanum tuberosum) (Solanaceae) at two temperatures. The predation rate of C. montrouzieri was measured using Petri dishes of 15 cm diameter with 1, 2, 4, 8, 16 and 24 adults of P. Citri. One third instar larva, one fourfh instar and one newly emerged adult (without differentiation of sex) of C. montrouzieri were added to each plate. The study was conducted in climatic chambers at temperatures of 25 and 30 º C and photophase of 12 hours. The predation rate was evaluated after 24 hours of prey exposition to the predator, by counting the number of preys trapped in the different treatments and control. The statistical design was completely randomized with four treatments x 6 subplots with 7 repetitions, the two temperatures. The values obtained were subjected to analysis of variance, to relate the number of scales preyed by larvae and adults of C. montrouzieri set up in different substrates. The amount of prey consumed by larvae and adults of the predator increased with increasing the prey density until it reaches a plateau, characterizing functional response type II. In general, the number of scales preyed by larvae and adults of C. montrouzieri was higher on potato and under temperature of 30 °C.
Functional response of mealybug destroyer preyng citrus mealybug under different temperatures and vegetable substrates
Keywords: Cryptolaemus montrouzieri; Planococcus citri; Potato; Pumpkin hybrid; Rangpur lime